Power control for full-duplex D2D communications underlaying cellular networks - Jihong ZHAO; Qiang HE; Hua QU; Zhirong LUAN (Dianxin kexue)
Device-to-device (D2D) communications that based on the wireless full-duplex transmission mode can not only reuse the cellular users' spectrum resource, but also significantly improve the spectral efficiency and the system throughout in wireless cellular networks. However, full-duplex D2D communications may generate same frequency interference to the reused cellular user (CU) while full-duplex D2D users share the same resources as CU in uplink. A low-complexity power control algorithm was proposed to maximize the full-duplex D2D links throughput while guaranteeing the quality of service(QoS)requirements for full-duplex D2D users and CU.Numerical results show that the proposed algorithm can improve the full-duplex D2D links throughput.Moreover,the performance of full-duplex D2D communications depend on the QoS requirements of CU, the distance of D2D pair and self-interference cancelation amounts.